2015
DOI: 10.1038/srep11210
|View full text |Cite
|
Sign up to set email alerts
|

Alpha or beta human chorionic gonadotropin knockdown decrease BeWo cell fusion by down-regulating PKA and CREB activation

Abstract: The aim of the present study is to delineate the role of human chorionic gonadotropin (hCG) in trophoblast fusion. In this direction, using shRNA lentiviral particles, α- and β-hCG silenced ‘BeWo’ cell lines were generated. Treatment of both α- and β-hCG silenced BeWo cells with either forskolin or exogenous hCG showed a significant reduction in cell fusion as compared with control shRNA treated cells. Studies by qRT-PCR, Western blotting and immunofluorescence revealed down-regulation of fusion-associated pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 43 publications
3
34
0
Order By: Relevance
“…It is also well known that trophoblast fusion stimulated by the protein kinase A pathway and cAMP involves the induction of GJA1 and hCG . Knockdown of their expression in the BeWo choriocarcinoma model results in an arrest of forskolin‐stimulated fusion, while overexpression of Cx43 permits Jeg‐3 cell fusion …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also well known that trophoblast fusion stimulated by the protein kinase A pathway and cAMP involves the induction of GJA1 and hCG . Knockdown of their expression in the BeWo choriocarcinoma model results in an arrest of forskolin‐stimulated fusion, while overexpression of Cx43 permits Jeg‐3 cell fusion …”
Section: Discussionmentioning
confidence: 99%
“…The role of P-gp in trophoblast fusion is less surprising as a number of studies have reported the loss or down-regulation of P-gp in the spontaneous differentiation of primary CT to ST. [40][41][42] It is also well known that trophoblast fusion stimulated by the protein kinase A pathway and cAMP involves the induction of GJA1 and hCG. 43 Knockdown of their expression in the BeWo choriocarcinoma model results in an arrest of forskolin-stimulated fusion, 44,45 while overexpression of Cx43 permits Jeg-3 cell fusion. 28 As a point of speculation, beyond its well-known role in substrate distribution and bioavailability and in multidrug resistance, P-gp plays a role in cancer cell invasion, drug resistance and metastasis.…”
mentioning
confidence: 99%
“…Forskolin, a pharmacological agent, is known to induce fusion of BeWo cells by activating cAMP and its downstream pathway . We have shown previously that treatment of BeWo cells with an optimized concentration of forskolin (25 μmol/L) led to ~20‐fold ( P = .02) and ~40‐fold ( P = .003) increase in the Wnt10b transcript at 24 and 48 hour, respectively, whereas transcript levels of Wnt 3, 4, 5a, 7b, and 11 were decreased significantly within 24 hour of forskolin treatment .…”
Section: Resultsmentioning
confidence: 92%
“…Forskolin, a pharmacological agent, is known to induce fusion of BeWo cells by activating cAMP and its downstream pathway . We have shown previously that treatment of BeWo cells with an optimized concentration of forskolin (25 μmol/L) led to ~20‐fold ( P = .02) and ~40‐fold ( P = .003) increase in the Wnt10b transcript at 24 and 48 hour, respectively, whereas transcript levels of Wnt 3, 4, 5a, 7b, and 11 were decreased significantly within 24 hour of forskolin treatment . As 14 Wnts are known to be expressed in the first trimester placenta, therefore, in the present study, we investigated the expression of rest of the eight Wnts (Wnt1, Wnt2, Wnt2b, Wnt5b, Wnt6, Wnt7a, Wnt9b, and Wnt10a) on treatment with 25 μmol/L of forskolin.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation